Hydrogen co-injection as a bridged technology for internal combustion engines - Molina-Ramírez, Sergio; Cortés-Reyes, Marina; Herrera-Delgado, María Concepción; Larrubia-Vargas, María Ángeles; Auñón-Hidalgo, Juan Antonio; Alemany-Arrebola, Luis José (International congress on Catalysis and Automotive Pollution Control – 12th edition CAPoC12, 2022)
In order to survive at media-term, diesel engines need a new approach for the use of the new fuel portfolio and to control the exhaust gas emissions. Hydrogen has been proposed as an alternative due to its excellent combustion properties, which could improve the combustion performance and emissions of internal combustion engines [1, 2]. The main drawback is that the location of a hydrogen cylinder inside the vehicles implies space and risk problems. Therefore, it could be produced on board and released into the air-intake of any biofuels fed to diesel engines. For that, the required optimized amount of hydrogen must be known, studying all engine parameters and emission in different driving modes for the establishment of the engine regions of operation in which partial replacement of fuel by hydrogen is effective as a bridged technology.
Keywords: Motores diesel; Hydrogen co-injectiion; Diesel engine; Bench motor engine; Zero emission